Answer:
10.36
Step-by-step explanation:
- $47 - $42.13 = $4.87
- ($4.87 ÷ $47) × 100 = 10.36%
B.) 81
sq rt of x= 12-3
sq rt of x=9
take the ^2 of both sides to get rid of the sq root
x^2= (9)^2
=81
Answer:
8x + 80
Step-by-step explanation:
positive side
Answer:
Step-by-step explanation:
Janelle expanded the expression as shown below. -4(-3x + 2/7) = -12x - 3 5/7 What errors did she make?
We are given the expression:
-4(-3x + 2/7)
Solving this expression:
Expanding the brackets
-4 × -3x + -4 × 2/7
12x - 8/7
12x - 1 1/7
Y/3 < -1
y < -1 * 3
y < -3
hope this helped, God bless!